A projection method for linear Fredholm–Volterra integro-differential equations. Issue 1 (11th December 2019) - İşler Acar, Neşe; Daşcıoğlu, Ayşegül
ABSTRACT: In this study, a collocation method, one of the type of projection methods based on the generalized Bernstein polynomials, is developed for the solution of high-order linear Fredholm–Volterra integro-differential equations containing derivatives of unknown function in the integral part. The method is valid for the mixed conditions. The convergence analysis and error bounds of the method are also given. Besides, six examples are presented to demonstrate the applicability and validity of the method.